Improving the filter system for the existing domestic waste pretreatment system in KUKTEM - Mohd Najid, Jamaludin (2006)
Water is the one of the resource that very important in our daily lives. However, if our water resources uses every day are polluted by contaminants, it can impacts for ecologies system life cycle and human life. The major pollutants are identified at Sungai Klang which the river are polluted by domestic activities around that area. However, local government was able expense a million Ringgit Malaysia (RM) to built water treatment system but it must be treated at the beginning point to make sure the water will exceed the water quality index specification. Therefore, early treatment or first stage of filter is very important before the domestic waste enter to the rivers. The main purpose of this study is to identified oil and grease on treated water after filtration process and propose of reuse water. Scope of this study was started at cafeteria student which oil interceptor was built. This study also improving the filter system for existing domestic waste pretreatment system(oil interceptor) that have be adaptation from mineral water port system that have being change their system. In design of filter, the material use on this design is defined in various size of aggregate and sand, which is tested to defined their infiltration rate (in/hr). Hopefully with this study, all parties will take part and involved in control pollution on our rivers.